Universalização do Ensino fundamental em Alagoas, rastreando modos e meios de sua efetivação pelo estudo de um caso - Oliveira, Cristina Maria Bezerra de (2010)
This work analyses the universal and municipal process of Ensino Fundamental in Alagoas (BR), from LDBEN/1996 and FUNDEF to 2008; taking as reference the high desertion, repetition and age/level distortion, which rate is concentrated in the Alagoas’ municipal systems. This research took from the historical aspects and the official documents conceptions, and it aims to understand the discussion about the educational public policy, considering the decentralization and municipalization character introduced in Brasil. It transferred the responsibilities to the state and municipal systems; mainly with the 14 constitutional amend the LDBEN 9394/96 and the law 9424/96, which established the FUNDEF, altering the federative relations, redistributing the attribute and the resource among the federal entities. Besides the bibliographical research which had got as main references the Brazilian constitution of 1988, the LDBEN/1996, the law 9424/96 (FUNDEF), Carvalho (2005), Davies (2001), Fávero (2005), Lira (2001), Santomé (2003) and Verçosa (2001), and, among them, the data analysis available in official documents and sites, the interview and questionnaire applied. It allows us to infer that in Alagoas, differently from other Brazilian states, this service, since the 70s, is being executed by the municipal systems, with FUNDEF, without having a qualitative gain.